The Formation of Students' Religious Character Through the Living Qur'an at Budi Satrya Junior High School - Aulia, Nurul; Nasution, Zulkipli (Journal of English Language and Education, 2025)
In the modern era of rapid scientific and technological progress, the development of student morals and character often lags behind, leading to behaviors inconsistent with religious principles such as disrespect, poor ethics, and a lack of empathy. This study posits that education is crucial in countering this trend by fostering religious character through the implementation of the Living Qur'an concept. Focusing on Budi Satrya Junior High School, this qualitative case study research investigates the process of building students' religious character. It describes the understanding of teachers and students regarding the Living Qur'an, identifies the religious principles being taught, and analyzes the teachers' role. Data were collected through observation, interviews, and documentation. The findings reveal that the Living Qur'an is perceived not merely as a literacy program but as an effort to internalize Qur'anic values in daily life. Instilled practices include reading short surahs, memorizing Juz 'Amma, reciting prayers and shalawat, performing Dhuha and congregational Zuhr prayers, memorizing Asmaul Husna, and participating in the Iqra' extracurricular. Teachers play a critical role as role models, guides, and motivators. The program's implementation has effectively created positive changes, evidenced by increased discipline, improved morals, and a stronger religious culture. Thus, the Living Qur'an is concluded to be an effective strategy for forming students into faithful, pious, and noble individuals.